Lecturer Performance Management in Higher Education: A Multi-Dimensional Perspective on the Tri Dharma - Mira Andriyani; Rusydi Ananda; Muhammad Rifai (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
This study aims to examine the quality of Tri Dharma of Higher Education implementation and the role of lecturer professional development in improving lecturer performance at two private Islamic higher education institutions: Institut Syekh Abdul Halim Hasan Binjai and Institut Jamiyah Mahmudiyah Langkat. A qualitative approach with a multi-site study design was employed. Data were collected through in-depth interviews with institutional leaders, lecturers, and LP2M administrators, classroom and academic activity observations, and document analysis, including lesson plans, lecturer performance reports, research publications, and community service records. The findings indicate that the implementation of Tri Dharma in the areas of teaching, research, and community service has been carried out systematically and in alignment with national higher education regulations. Lecturer professional development programs—such as training, workshops, research mentoring, and performance evaluation systems—significantly contribute to enhancing teaching quality, research productivity, and community engagement. Despite institutional differences in implementation strategies, both institutions demonstrate that strong institutional commitment and lecturers’ intrinsic motivation are critical determinants of sustainable Tri Dharma performance. This study highlights the strategic importance of lecturer professional development in strengthening academic quality and institutional competitiveness.